ASSESSMENT OF THE AMBIENT BACKGROUND RADIATION LEVELS AT THE TAKE-OFF CAMPUS OF FEDERAL UNIVERSITY DUTSIN-MA, KATSINA STATE-NIGERIA - Tikyaa, E. V.; Atsue, T.; Adegboyega, J. (FUDMA JOURNAL OF SCIENCES, 2023)
This study investigates the ambient background radiation levels at the take–off campus of Federal University Dutsin–Ma (FUDMA), Katsina State in order to measure the indoor and outdoor radiation levels using a digital radiation meter (Radiation Alert Inspector). The radiation meter was held one meter above the ground and the ambient radiation levels in thirty-six (36) buildings, some road pavements and outdoor sports facilities were surveyed. The results obtained showed that, the Old Biology laboratory and Biochemistry laboratory were found to have the highest values of indoor annual equivalent dose rate of 2.27±0.29 and 2.27±0.33 respectively, while the lowest value for indoor annual equivalent dose rate was recorded as 0.85±0.22 at Lecture Halls 3 and 4. For the outdoor facilities, the main gate road pavement was found to have the highest mean effective dose of 0.24 while the Handball court had the lowest mean effective value of 0.16 . For the block of offices, the Senate Building recorded the highest indoor annual equivalent dose rate of 1.63±0.34 while Blocks B and Block D recorded the lowest values of 1.04±0.31 and 1.04±0.40 respectively. The overall average indoor and outdoor annual equivalent dose rates on the take-off site of FUDMA were computed and found to be 1.41±0.29 and 0.33±0.08 respectively. The correlation coefficient of 0.1846 was obtained indicating a weak relationship between the indoor and outdoor background radiation levels. A comparison of these results with the worldwide average limit of equivalent dose rate of 2.4 recommended by the International Commission on Radiation